Autonomous Wildlife Deterrent System (AWDS) / Muhammad Afiq Muhammad Nazri ... [et al.] - Muhammad Nazri, Muhammad Afiq; Mohd Hazuhaini, Haekal Erfan; Shaifful Azzwan, Aina Shafiza; Abd Hafidz, Amylea Nadzirah (2024)
The Autonomous Wildlife Deterrent System (AWDS) is a cutting-edge solution developed by students from the College of Built Environment, Universiti Teknologi MARA, to address the escalating issue of human-wildlife conflicts. By leveraging advanced detection sensors, artificial intelligence (AI) algorithms, and automated deterrents, the AWDS aims to proactively prevent wildlife from encroaching into human-inhabited areas. This innovative system not only enhances safety for both humans and wildlife but also promotes harmonious coexistence by minimising conflict incidents. With features such as real-time monitoring, species identification, and environmentally sustainable power sources, the AWDS offers a comprehensive and effective approach to mitigating human-wildlife conflicts.